Future Airports Development Strategies - Antonin Kazda; Benedikt Badanik; Anna Tomova; Isabelle Laplace; Nathalie Lenoir (Communications - Scientific letters of the University of Zilina, 2013)
Air transport was traditionally highly regulated, fragmented and protected. With European air transport market deregulation in the mid 1980s also airports could respond to new factors. Methodology developed within the FAST project analyzed evolution of airport strategies potential in the forthcoming decade in the frame of new airport typology reflecting different strategies depending on the airport size, market type and market potential.